Strategi Universitas Dehasen Bengkulu Dalam Meningkatkan Jumlah Mahasiswa (Studi pada Bidang Kemahasiwaaan Universitas Dehasen Bengkulu) - Dahlia, Dahlia; Sutardi, Dodo; Sakti, Budiman (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Education is currently the cornerstone of sustainable development in Indonesia. However, until now public services, especially in education, are still uneven. Therefore, Indonesia prioritizes education goals in the SDGs, especially SDG 4 which emphasizes equitable quality education and equitable access to education. One factor in improving quality can be seen from the increase in the number of students so as to realize the vision of inclusive education. Dehasen University is currently experiencing an increase in the number of students from 2020 to 2022. Therefore, researchers will conduct research using SWOT analysis to identify internal and external factors that affect the increase in student numbers. The result is that Dehasen University has strengths in a very consistent student admission team, wide internet access and a very strategic location. However, the weaknesses are the low cost of promotion, facilities that are currently inadequate and the lack of mastery of digital technology by some staff. Opportunities include the current great interest of the community to continue their studies, the development of technology and a wide network of alumni. The threats themselves include competition for student recruitment, demands for improving the quality of graduates and uncertainty in the economy. So it is recommended that universities can utilize internal strengths in overcoming external challenges and be able to implement strategies that have the benefits of external opportunities. So, Dehasen university is able to continue to increase students while overcoming the challenges faced.